THE CORRELATION BETWEEN STUDENTS’ GRAMMAR MASTERY AND NEWS WRITING ABILITY - Etfita, Fauzul (STAI Hubbulwathan Duri, 2019)
The objective of this research was to find out the correlation between students’ grammar mastery and News writing ability of the fourth semester students of English Language Education at Faculty of Teachers’ and Training Universitas Islam Riau. This research used correlation research design. The research sample was 4C Class which consisted of 26 students which selected by using cluster sampling technique. Technique of data collection was grammar and news writing tests. In analysing the data, the researcher applied Pearson’s Product Moment Correlation Coefficient and Significance of Coefficient Correlation formula. The result of calculating correlation between students’ grammar mastery and their achievement in News writing was r = 0.874. It means that there is a significant correlation between students’ mastery of grammar and News writing ability of the fourth semester students of English Language Education at Faculty of Teachers’ and Training Universitas Islam Riau